Oridonin induces growth inhibition and apoptosis in human gastric carcinoma cells by enhancement of p53 expression and function - Bi,Enxu (2018)
The tumor suppressive role of oridonin, an active compound extracted from Rabdosia rubescens, has been proven in several gastric cancer (GC) cell lines. The present study aimed to evaluate the effect of oridonin on another GC cell line, SNU-216, and explore the potential mechanisms. The viable cell numbers, cell migration, survival fraction, and cell viability were, respectively, evaluated by trypan blue exclusion assay, wound healing assay, clonogenic assay, and CCK-8 assay. Cell apoptosis was determined by flow cytometry assay and western blot. The expression of p53 was inhibited by transient transfection, and the efficiency was verified by western blot. qRT-PCR was performed to measure the mRNA expression of p53. Western blot was used to evaluate the protein expression of apoptosis, DNA damage and p53 function related factors. We found that oridonin significantly inhibited cell proliferation, migration, and survivability, and enhanced cell apoptosis in SNU-216 cells. However, it had no influence on HEK293 cell viability. Oridonin also remarkably enhanced the anti-tumor effect of cisplatin on SNU-216 cells, as it significantly increased apoptotic cells and decreased cell viability. Moreover, the mRNA and protein expression of p53 was significantly up-regulated in oridonin-treated cells, while Mdm2 expression was down-regulated. Furthermore, oridonin enhanced p53 function and induced DNA damage. Knockdown of p53 or employing the caspase inhibitor, Boc-D-FMK, reversed the effect of oridonin on cell viability and apoptosis-related protein expression. The present study demonstrated that oridonin exhibited an anti-tumor effect on GC SNU-216 cells through regulating p53 expression and function.